1987
DOI: 10.1104/pp.85.1.243
|View full text |Cite
|
Sign up to set email alerts
|

Photocontrol of Sorghum Leaf Phosphoenolpyruvate Carboxylase

Abstract: The mechanism underlying the light effect on phosphoenolpyruvate carboxylase (PEPC) from the C-plant sorghum (Sorgkwm vulgare Pers., var

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…However, those seedlings which received an additional far-red treatment showed a reversal in sucrose-P synthase activity by 2 h postillumination, resulting in an approximately 50% decrease in enzyme activity. These data demonstrate the reversibility of sucrose-P synthase activity by illumination with red followed by far-red and further supports the hypothesis that phytochrome may be involved in light dependent changes in sucrose-P synthase activity in maize (16).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…However, those seedlings which received an additional far-red treatment showed a reversal in sucrose-P synthase activity by 2 h postillumination, resulting in an approximately 50% decrease in enzyme activity. These data demonstrate the reversibility of sucrose-P synthase activity by illumination with red followed by far-red and further supports the hypothesis that phytochrome may be involved in light dependent changes in sucrose-P synthase activity in maize (16).…”
Section: Resultssupporting
confidence: 85%
“…The other form found in greening leaves was designated G-PERPC and occurred only after etiolated leaves were exposed to light. Later, Thomas et al (16) showed that the activity of G-PEPC was sensitive to red and far-red treatments. A 10-min exposure to red stimulated G-PEPC, whereas far-red (either alone or following a red treatment) caused a substantial inhibition of the G-PEPC isoform.…”
mentioning
confidence: 99%
“…Nagy et al (1988), however, found no diurnal changes in the level of wheat SSu mRNA. The transcriptional activity of PEPC, another lightinduced gene family (Nelson et al, 1984;Thomas et al, 1987), also showed no diurnal fluctuations (Figure 1). Whether these differences reflect differences between monocots and dicots or between plant species or are due to differences in sensitivity of experimental technique remains to be seen.…”
Section: Discussionmentioning
confidence: 97%
“…The mechanism of light modulation was somewhat clarified by Monreal and colleagues [31], who elaborated on the participation of PLD and PA in the signaling cascade of light-dependent upregulation of a sorghum leaf PEPC. It has been proposed that a light signal is the primary event that leads to the activation of phospholipase C and the synthesis of PEPC-PK in the mesophyll of C 4 plants [41]. It was also shown that light increased the PLD activity and production of PA in sorghum leaf discs, thus supporting a link between PLD-dependent PA production and a light signal [31,42].…”
Section: Posttranslational Modifications (Ptms): Phosphorylation and Monoubiquitination Of Pepcsmentioning
confidence: 91%